The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11104-021-05043-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated field assessment of nitrogen release dynamics and crop recovery of band-applied controlled-release fertilisers

Abstract: and two PCU products) were replicated four times. Soil samples were collected at 8, 27, 48, 82 and 173 days after fertiliser application (DAF) to quantify N release dynamics. Maize biomass production, N uptake, grain yield and N content were quantified to assess the agronomic performance of CRFs relative to standard urea. Results CRFs delayed the release of N relative to standard urea. Soil moisture and mass flow impacted N release dynamics from fertiliser bands, with soil chemical changes largely confined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Similar findings have been reported with irrigated maize for both DMPP-urea or CRF products (Dang et al, 2021;Martinez et al, 2021). However, several trials in sugarcane (Dowie et al, 2019;Wang et al, 2016a), which has a longer N-uptake period, reported similar crop N uptake from lower rates of DMPP-urea than from urea applied at rates 20-25% higher (i.e., industry-standard rates), resulting in greater NUE with this EEF.…”
Section: Reduced N Losses May Not Always Translate Into Improved Crop...supporting
confidence: 76%
See 2 more Smart Citations
“…Similar findings have been reported with irrigated maize for both DMPP-urea or CRF products (Dang et al, 2021;Martinez et al, 2021). However, several trials in sugarcane (Dowie et al, 2019;Wang et al, 2016a), which has a longer N-uptake period, reported similar crop N uptake from lower rates of DMPP-urea than from urea applied at rates 20-25% higher (i.e., industry-standard rates), resulting in greater NUE with this EEF.…”
Section: Reduced N Losses May Not Always Translate Into Improved Crop...supporting
confidence: 76%
“…Recently, concerns of polymer "shell" persistence and the potential for these to carry unreleased N into natural ecosystems (Azeem et al, 2014;Trenkel, 2010) has led to investigation of a range of biodegradable coatings (Araujo et al, 2017;Li et al, 2016;Rotondo et al, 2018;Vadjung and Saengsuwan, 2018). Environmental concerns will continue to drive the development of biodegradable coatings in future CRF products, but the efficacy of these coatings for delivering a controlled release of N has only been explored in a very limited number of studies (e.g., Martinez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [ 21 ] deemed that a certain level of N being present would accelerate cotton lateral root elongation and that of the root-projected area by regulating abscisic acid and salicylic acid. Base ions and N in soil, however, are highly mobile and show uneven spatial distributions with obvious spatiotemporal variations [ 22 , 23 ]. To adapt to the non-homogeneity of nutrients and salt, root growth might show a strong plasticity response [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mitigating the loss of fertilizer-derived N (fertilizer-N) and/or improving NUE has become the focus of considerable agronomic research attention. Subsequently, the development of high-efficiency N fertilizer has emerged as one of the most effective approaches [5,6]. For example, the modification of urea fertilizer with nutrient enhancers has gained popularity among fertilizer researchers and manufacturers because it requires relatively low inputs to induce high increases in NUE [7,8].…”
Section: Introductionmentioning
confidence: 99%